Using qualitative research articles to talk about gender and race inequities in health care. Issue 4 (1st October 2020) - Wright, Kallia O.; Dagan, Kelly A.
Abstract : Using peer-reviewed articles, this activity informs students of experiences female-identifying patients encounter in health-care contexts. The activity draws the students' attention to gendered and racial prejudices and how those could impact patients' relationship with practitioners. Courses: Suitable for undergraduate courses, such as Gender and Women's Studies, Interpersonal Communication, Medical Sociology, Communication Research Methods, Health Communication, Qualitative Research Methods, Race and Ethnicity, and Sociology of Gender. Objectives: After completing this unit activity, students will learn how to (1) analyze the impact of race and gender on patients, (2) advocate for female-identifying patients, (3) help create more welcoming and equitable interactions in health care, and (4) advocate for themselves within the health-care context.